Use of Animated Videos to Increase Learning Interest of SDN 2 Cikembulan Students in Natural and Social Science Subjects - Widuri, Lilis; Ardy Wiyani, Novan (International Proceedings of Nusantara Raya, 2024)
This study discusses the effect of animated videos on the learning interest of grade V students of SDN 2 Cikembulan in the subject of Natural and Social Sciences (IPAS). Lack of student involvement in the learning process is a crucial problem that results in low student productivity in education. The purpose of the study was to determine the effect of animated videos on increasing student interest in learning. The research method used is a qualitative method with purposive sampling technique, the sample and research population are grade V students of SDN 2 Cikembulan. Data collection instruments were questionnaires and student ability tests. The results showed that the learning method with animated videos contributed significantly to student activeness in social studies subjects. In addition, students' understanding was also measured through ability tests which showed an increase in students' understanding of the subject matter of Natural and Social Sciences (IPAS).